The prediction of permanent deformation in flexible pavements - Bell, C.A. (1978)
At the present time (1978) new roads in the United Kingdom are designed empirically. However, over approximately the last twenty years pavement technologists throughout the world have been advocating fundamentally based procedures. Such procedures, when applied to flexible pavements, require a detailed knowledge of the two main modes of failure, fatigue of the bituminous bound layers and excessive permanent deformation of the pavement as a whole.